Suppression of FOXO1 activity by FHL2 through SIRT1-mediated deacetylation - Yang, Yonghua (2005)
Forkhead box class O (FOXO) proteins are transcription factors that function downstream of the PTEN tumor suppressor and directly control the expression of genes involved in apoptosis, cell cycle progression, and stress responses. In the present study, we show that FOXO1 interacts with four and a half LIM 2 (FHL2) in prostate cancer cells. This interaction occurred in the nucleus and was enhanced by lysophosphatic acid. FHL2 decreased the transcriptional activity of FOXO1 and the expression of known FOXO target genes and inhibited FOXO1-induced apoptosis. Interestingly, SIRT1, a mammalian homolog of yeast Sir2, bound to and deacetylated FOXO1 and inhibited its transcriptional activity. FHL2 enhanced the interaction of FOXO1 and SIRT1 and the deacetylation of FOXO1 by Sirtuin-1 (SIRT1). Overall, our data show that FHL2 inhibits FOXO1 activity in prostate cancer cells by promoting the deacetylation of FOXO1 by SIRT1.